Gendered Spaces: Social Conflict in Women’s Weight Training - Utami, Lingga; Maftuh, Bunyamin; Malihah, Elly (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2024)
This research aims to understand the conflicts experienced by women in fulfilling the role of a mother while striving to remain active in fitness centers. Alongside the demands of the dual role as a mother and an individual concerned about health, many women experience conflicts between family responsibilities and the desire to engage in physical activity. This study employs a qualitative approach with data collection techniques such as observation, in-depth interviews, and literature review. The research participants are women with experience in navigating this dual role. The findings of this research reveal various factors contributing to women's conflicts in maintaining their health and fitness. These factors include tight time demands, limited social support, feelings of guilt, and body perceptions. Additionally, the study identifies strategies used by women to overcome these conflicts, such as scheduling wisely, seeking family support, and identifying personal priorities. This research provides valuable insights into the challenges faced by women in juggling the dual role of being a mother and an active individual in fitness. The results can be utilized to develop support programs and policies that encourage women in pursuing a healthy lifestyle while fulfilling their family responsibilities